Hubungan antara literasi sains dan keterampilan proses sains terhadap hasil belajar kognitif hots mahasiswa pgsd - Hanifaw Rahma Setyaningrum; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Universitas Sebelas Maret, 2024)
This research aims to determine the relationship between scientific literacy and science process skills on HOTS cognitive learning outcomes of PGSD students. The research design is correlational, utilizing tests for data collection. The population consists of all 2022 PGSD UNS students, with random cluster sampling used for sampling. Data analysis employs multiple correlation analysis. The results indicate a positive and significant relationship between science literacy and science process skills on HOTS cognitive learning outcomes, with a significance value of 0.000 < 0.05 and a Pearson correlation value of 0.495. This research indicates that as students' science literacy increases, their HOTS cognitive learning outcomes also improve. Additionally, an increase in students' science process skills is followed by an improvement in HOTS cognitive learning outcomes. This can enhance students' knowledge and awareness, enabling them to explore and understand scientific phenomena through direct experience and interaction with the environment.